THE KOREAN WAVE PHENOMENA IN YOUTH AND HALAL INDUSTRY: OPPORTUNITIES AND CHALLENGES - Hutama Syam, Ananta Prayoga; Ichwan, Moch Nur (Likuid Jurnal Ekonomi Industri Halal, 2023)
Korean culture was caused by the Korean wave or Hallyu wave that entered and spread among young people in Indonesia. The halal industry is considered an industry that can answer their needs and desires in this era of the booming Korean wave. The purpose of this study is to determine the impact of the Korean cultural phenomenon caused by the Korean wave on the economic, social, and consumptive cultural aspects of the younger generation, and to analyze the opportunities and challenges for the halal industry in dealing with this phenomenon. The method in this study is the netnographic method carrying out data collection techniques carried out by observing online and observing the facts in the field. Other supporting data sources are obtained from literature studies, be it journals, books or articles, and other writings. The results of this study indicate that Korean culture spreads to all aspects of the life of the younger generation who behave consumptively due to the bandwagon effect, from food, and drink to fashion. Opportunities for the halal industry are halal food gastro-diplomacy, Korean halal festivals event and the use of online media. While the challenges include the legality of thrifting products, imported ingredients that are not halal, the low awareness of halal by the younger generation and the dualism in halal certification.